British Law and Governance in Treaty Port China 1842-1927: Consuls, Courts and Colonial Subjects - Thompson, Alexander (Imperialism in East Asia, 2024)
In putting extraterritoriality into practice in the treaty ports, the British state did not simply withdraw rights from the Chinese state; it inhabited the space made by extraterritoriality by building institutions and engaging in practices which had consequences for the development of the treaty ports, and which need to be at the forefront of any attempt to understand colonialism in China. Through a focus both on the creation of law and institutions, and also on the management of British ‘problem populations’ – violent Europeans and ‘martial’ Indians – this book provides a revision of the history of empire and colonialism in China, explaining important features which have to date been glossed over in studies of other aspects of treaty port colonialism. Colonialism in China casts a long shadow, but key aspects of the British state’s central role in this history have before now been little understood.